LARANGAN TENTANG POLITIK UANG DAN BIAYA (COST) POLITIK OLEH PASANGAN CALON/PARTAI POLITIK DALAM MASA KAMPANYE PEMILIHAN KEPALA DAERAH DI KABUPATEN SAMOSIR - Situmorang, Arta Uli LCP; Nasution, Mirza; Sihombing, Eka N.A.M (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
In the context of the 2024 regional electrions, the practice of money politics is expected to remain a key strategy used by various political actors to influence election results. The political reality in Indonesia shows that regional elections are often marred by various challenges, one of which is the phenomenon of money politics. Money politics poses a serious threat to election integrity because it has the potential to undermine democratic values and reduce the quality of public political participation. Voter behaviour in determining political choices generally tends to be influenced by material factors, such as the gift or money or goods in the lead-up to the election, rather than by rational consideration of the vision, mission, and policy programs offered by the candidates. In the process of organizing regional elections in Indonesia, there are election management bodies, namely the General Elections Commission (GEC), the Election Supervisory Agency, and the Election Organizer Honorary Council (EOHC). The GEC has the duty and authority as an election management body to prepare for all stages of the election process.